Perlakuan Akuntansi untuk Aset Bersejarah pada Situs Bung Karno Kabupaten Ende - Iriany Dewi Soleiman (ANALISIS, 2019)
This research aims to determine the accounting treatment for historical assets on the site of the PSAP of the Bung Karno Ende reviewed from 2010 (in terms of recognition, measurement, presentation and historical asset disclosure) this research is a Qualitative research using a case study approach to the Financial Management Agency and the regional assets of Ende Regency. Data collection is done using observation methods, interviews and documentation. Data analysis techniques used are qualitative descriptive. The results of this study showed that the regional Asset Finance Management Agency (BPKAD) Ende Regency, has not implemented the accounting treatment of historical assets of the site of Bung Karno in accordance with PSAP No. 07 year 2010. It can be seen as follows, BPKAD recognizes the site of Bung Karno is a historical asset is not a obligation because it has historical value and it is difficult to estimate the period of its benefits, but in terms of historical asset measurement of the site of Bung Karno judged only Buildings and buildings but the historical values have not been presented with zero value and are not disclosed in the records of the financial statements.